EFFECT OF DIFFERENT LEVELS OF DIGESTIBLE THREONINE ON GROWTH PERFORMANCE OF BROILER CHICKS - A. R. Khan; H. Nawaz.; I. Zahoor (Journal of Animal and Plant Sciences, 2006)
This investigation was carried out to determine the effects of different levels of digestible threonine on growth performance, dressing percentage and breast meat yield of broiler chicks. One hundred and twenty day old chicks were randomly divided into four groups A, B, C and D which were fed on four diets having (CP 21% and ME 2950 Kcal/kg) with four different levels of digestible threonine 0.678, 0.728, 0.778 and 0.828 % of the dietary CP respectively. On 35th day at the end of the experiment it was observed that the weight gain, feed consumption, FCR, dressing %age and breast meat yield were significantly (P<0.05) differed among the experimental groups. The weight gain and feed consumption was increased with an increase in digestible threonine level except the group B in which these parameters were decreased. The group B fed on diet containing digestible threonine level (0.728%) gives best dressing %age, breast meat yield and FCR value. The results of the present study showed that the digestible threonine level (0.728%) gives the best result than other levels.
Keywords: Feed conversion ratio; Crude protein; Metabolizable energy